Effect of different composite modulation protocols on the conversion and polymerization stress profile of bulk-filled resin restorations. Issue 7 (July 2020) - Erhardt, M.C.G.; Goulart, M.; Jacques, R.C.; Rodrigues, J.A.; Pfeifer, C.S.
Highlights: Pre-heating does not reduce polymerization stress of resin composite restorations. Thio-urethane addition increases resin composite degree of conversion. Thio-urethane addition reduces resin composite polymerization stress. Abstract: Objective: The aim of this in vitro study was to test the effect of different composite modulation protocols (pre-heating, light-curing time and oligomer addition) for bulk filling techniques on resin polymerization stress, intra-pulpal temperature change and degree of conversion. Methods: Class I cavities (4 mm depth × 5 mm diameter) were prepared in 48 extracted third molars and divided in 6 groups. Restorations were completed with a single increment, according to the following groups: (1) Filtek Z250XT (room temperature – activated for 20 s); (2) Filtek Z250XT (at room temperature – activated for 40 s); (3) Filtek Z250XT (pre-heated at 68 °C – activated for 20 s); (4) Filtek Z250XT (pre-heated at 68 °C – activated for 40 s); (5) Filtek BulkFill (at room temperature – activated for 20 s); (6) Filtek Z250XT (modified by the addition of a thio-urethane oligomer at room temperature – activated for 40 s). Acoustic emission test was used as a real-time polymerization stress (PS) assessment. The intra-pulpal temperature change was recorded with a thermocouple and bottom/top degree of conversion (DC) measured by Raman spectroscopy. Data were analyzed with one-way ANOVA/Tukey's test ( α  = 5%). Results: Pre-heating the resin composite did not influence the intra-pulpal temperature ( p  = 0.077). The thio-urethane-containing composite exhibited significantly less PS, due to a lower number of acoustic events. Groups with pre-heated composites did not result in significantly different PS. Filtek BulkFill and the thio-urethane experimental composite presented significantly higher DC. Significance: Resin composite pre-heating was not able to reduce polymerization stress in direct restorations. However, thio-urethane addition to a resin composite could reduce the polymerization stress while improving the DC.